Storms, early education, and human capital - Martino Pelli; Jeanne Tschopp (Asian Development Bank (ADB), 2024)
This paper explores how school-age exposure to storms impacts the education and primary activity status of young adults in India. Using a cross-sectional cohort study based on wind exposure histories, we find evidence of a significant deskilling of areas vulnerable to climate change-related risks. Specifically, our results show a 2.4 percentage point increase in the probability of accruing educational delays, a 2 percentage point decline in post-secondary education achievement, and a 1.6 percentage point reduction in obtaining regular salaried jobs. Additionally, our study provides evidence that degraded school infrastructure and declining household income contribute to these findings.
Keywords: I25; O12; Q54; 330; climate change; storms; education; human capital